Correction: Microchip in situ electrosynthesis of silver metallic oxide clusters for ultra-FAST detection of galactose in galactosemic newborns' urine samples. Issue 19 (12th September 2017) - García-Carmona, Laura; Rojas, Daniel; González, María Cristina; Escarpa, Alberto
Abstract : Correction for 'Microchip in situ electrosynthesis of silver metallic oxide clusters for ultra-FAST detection of galactose in galactosemic newborns' urine samples by Laura García-Carmona et al., Analyst, 2016, 141, 6002–6007.